Polycystic ovary syndrome (PCOS) - risk factor, diagnostic and current treatment - Justyna Wojcik; Aleksandra Obuchowska; Alicja Ozga; Arkadiusz Standyło; Karolina Obuchowska; Paulina Piotrowska (Kazimierz Wielki University, 2020)
Introduction:   Polycystic ovary syndrome (PCOS) is one of the most common endocrine and metabolic disorders in women in reproductive age, defined as a combination of signs and symptoms resulting from androgen excess and ovarian dysfunction in the absence of other specific diagnoses. PCOS is often associated with an increased risk of obesity, insulin resistance, metabolic disorders and cardiovascular events.   The aim of the study:  The purpose of this systemic review was to collect and analyze materials about risk factors, diagnostics, and the current treatment of polycystic ovary syndrome. Material and method:  Review of the literature published in 2004-2018. Description of the state of knowledge:  PCOS is characterized by an excessive secretion of androgens from the ovaries and / or adrenal glands. Intrinsic ovarian factors, such as altered steroidogenesis, and factors external to the ovary, such as hyperinsulinemia, contribute to the ovarian overproduction of androgens. PCOS requires careful selection of an appropriate diagnostic method and therapeutic approach to combat hyperandrogenism, a consequence of ovarian dysfunction and related metabolic disorders. Treatment of both women at risk of PCOS and those with a confirmed diagnosis of PCOS includes education, healthy lifestyle interventions and symptomatic therapeutic interventions. Summary:   PCOS is a complex disorder involving many organs and affecting many body functions. It is important to diagnose this disease as soon as possible in order to implement appropriately selected therapeutic treatment aimed at eliminating disease symptoms and reducing the systemic consequences of hyperandrogenism in patients.